Advanced Semiconductor Heterostructures: Novel Devices, Potential Device Applications and Basic Properties (Selected Topics in Electronics and Systems) - Michael A Stroscio (World Scientific, 2003)
This volume provides valuable summaries on many aspects of advanced semiconductor heterostructures and highlights the great variety of semiconductor heterostructures that has emerged since their original conception. As exemplified by the chapters in this book, recent progress on advanced semiconductor heterostructures spans a truly remarkable range of scientific fields with an associated diversity of applications. Some of these applications will undoubtedly revolutionize critically important facets of modern technology. At the heart of these advances is the ability to design and control the properties of semiconductor devices on the nanoscale. As an example, the intersubband lasers discussed in this book have a broad range of previously unobtainable characteristics and associated applications as a result of the nanoscale dimensional control of the underlying semiconductor heterostructures. As this book illustrates, an astounding variety of heterostructures can be fabricated with current technology; the potentially widespread use of layered quantum dots fabricated with nanoscale precision in biological applications opens up exciting advances in medicine. In addition, many more excellent examples of the remarkable impact being made through the use of semiconductor heterostructures are given. The summaries in this volume provide timely insights into what we know now about selected areas of advanced semiconductor heterostructures and also provide foundations for further developments.